English Teachers' Techniques and Approaches for Teaching Reading Comprehension in Ghanaian Senior High Schools - Oppong-Poku, Kathy; Sevnarayan, Kershnee (Universitas Islam Negeri Walisongo Semarang, 2024)
The declining performance of Senior High School English second-language learners in English-language examinations in Ghana has raised concerns about the effectiveness of teaching methods. Despite existing research on instructional strategies, there is a paucity of studies examining the specific techniques and approaches SHS teachers use to improve English reading comprehension among second-language learners. This study aimed to investigate the teaching techniques and approaches used by senior high school teachers in Ghana to enhance English reading comprehension, identify factors that influence the choice of technique, and explore teachers’ perceptions of their influence on learner learning outcomes. A qualitative case study design was employed, with purposeful sampling. The study adopted a constructivist approach to discuss the findings. Data were collected through focus group discussions and in-depth interviews with nine teachers from two schools. The findings revealed that teachers employed various techniques, included silent reading, scanning, skimming, and combination approaches. Skimming and scanning techniques were most preferred. Factors influencing technique choice included medium of instruction, teacher proficiency, and textbook availability. Learner's disinterest in reading emerged as a significant challenge. The study emphasizes the importance of teacher training, the accessibility of educational resources, and strategies to foster learner engagement. Findings inform educational policy and practice, emphasizing the importance of addressing English second language teacher capacity, resource availability, and learner motivation to improve English language learning outcomes.